Folk Oral Personal Experience Stories: Communicative Conventions and Narrative Strategies - Veselova, Inna (2019)
The subject of the article is the communicative and narrative parameters of oral personal supernatural experience stories. The study is based on the corpus of oral stories about contacts with supernatural forces or creatures, as well as about watching the signs of destiny, recorded in interviews which have taken place in the villages of the North of Russia (Archangel and Vologda Regions) during folklore anthropologic expeditions of the last 40 years. Interviews are stored in the Folklore Archive of St. Petersburg State University and in the Electronic Database “Russian Day-to-day Life”. The majority of stories about encounters with the supernatural, transcribed word for word, turn out to be not the consecutive and logical account of events but a chain of remarks by the event participants and the narrator’s comments to such remarks like dramatic performances. Oral supernatural narratives have more complicated composition then “classic” von Sydow “the first person” and “the third person” schemes. We are dealing with the type of narrative whose events occurred regarding the third person, but whose story is told in the first person with constant 32 Inna Veselova references to the original narrator. In every story we hear the chorus of different voices: of witnesses, interpreters, advisers – co-participants in events and experience. We may suggest that the more literary, formal and written a culture becomes, the fewer number of voices is heard in performance and the more narrator-concentratedand the less polyphonic is the story.
Keywords: folk prose; Russian folklore; field material; oral personal stories; supernatural experience; communicative parameters; performance budget; polylogue form; communicative levels of folk narrative